Targeting Molecular Chaperones for the Treatment of Cystic Fibrosis: Is It a Viable Approach? - Heard, Ashley; Thompson, Jake; Carver, Jessica; Bakey, Michelle; Robert Wang, X. (Current Drug Targets, 2015)
Cystic Fibrosis (CF) is largely caused by protein misfolding and the loss of function of a plasma membrane anion channel known as the cystic fibrosis transmembrane conductance regulator (CFTR). The most common CF-causing mutation, F508del, leads to severe conformational defect in CFTR. The cellular chaperone machinery plays an important role in CFTR biogenesis and quality control. Multiple attempts have been made to improve the cell surface functional expression of the mutant CFTR by modulating the expression of components of the cellular chaperone machinery. The efficacy of such an approach has been low largely due to the severe intrinsic folding defects of the F508del CFTR. Moreover, the impact of chaperone perturbation on the chaperone machinery itself and on other physiologically important proteins might lead to potentially severe side effects. Approaches aimed at disrupting chaperone-CFTR interactions show greater efficacy, and are compatible with small-molecule drug discovery and gene therapy. Combination between chaperone modulators and F508del correctors might further enhance potency and specificity. As molecular chaperones play important roles in regulating inflammation and immunity, they can be potential targets for controlling airway infection and inflammation in patients. If such effects can be synergized with chaperone-mediated regulation of CFTR biogenesis and quality control, more efficacious therapeutics will be developed to combat CF lung disease.
Keywords: cystic fibrosis